The challenge of Helicobacter pylori resistance to antibiotics: the comeback of bismuth-based quadruple therapy - Mégraud, Francis (SAGE Publications, 2012)
A proton-pump inhibitor (PPI), clarithromycin-based, triple therapy has been the recommended treatment for Helicobacter pylori eradication for the past 15 years. Due to a steady increase in H. pylori resistance to clarithromycin, this triple clarithromycin-based treatment has become progressively less efficacious. Several approaches are available to address this situation: one is to test for clarithromycin resistance so that this triple clarithromycin-based regimen is given only to those who will benefit; a second is to prescribe the drugs sequentially, beginning with amoxicillin and a PPI followed by clarithromycin and metronidazole, again with a PPI or the four drugs prescribed concomitantly; a third alternative is to use bismuth-based quadruple therapy, PPI plus a standardized three-in-one capsule, bismuth subcitrate potassium, metronidazole, and tetracycline (BMT, sold under licence as Pylera®). The advantages of these different approaches are reviewed, including the relevance of BMT three-in-one capsule in clinical practice.